2004
DOI: 10.1083/jcb.200406115
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic pathways are selectively activated by granzyme A and/or granzyme B in CTL-mediated target cell lysis

Abstract: Purified cytolytic T lymphocyte (CTL) proteases granzyme (gzm)A and gzmB with sublytic dose of perforin (perf) initiate distinct proapoptotic pathways. Their physiological relevance in CTL-mediated target cell apoptosis is elusive. Using ex vivo virus-immune CD8+ T cells from mice deficient in perf, gzmA and/or gzmB, and the Fas-resistant EL4.F15 tumor target cell, we show that (a) CTL from gzmA−/− or gzmB−/− mice similarly induced early proapoptotic features, such as phosphatidyl serine (PS) exposure on plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
184
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(197 citation statements)
references
References 69 publications
13
184
0
Order By: Relevance
“…Using this distinct morphology to specifically identify cells undergoing GzmA-mediated death, we analysed hundreds of individual cellular deaths to clarify the molecular mechanisms that were consistently and authentically associated with it. Our finding that GzmA induces a caspase-independent form of death without cytochrome c release agrees with previous findings, 4,5,12 but our finding that it did not involve membrane blebbing, early DC m loss or early ROS production contrasts with others. 4,5 The absence of mitochondrial damage during the early stages of GzmB À / À NK-mediated cell death was unexpected, given its prominent role in initiating the GzmA cell death pathway.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Using this distinct morphology to specifically identify cells undergoing GzmA-mediated death, we analysed hundreds of individual cellular deaths to clarify the molecular mechanisms that were consistently and authentically associated with it. Our finding that GzmA induces a caspase-independent form of death without cytochrome c release agrees with previous findings, 4,5,12 but our finding that it did not involve membrane blebbing, early DC m loss or early ROS production contrasts with others. 4,5 The absence of mitochondrial damage during the early stages of GzmB À / À NK-mediated cell death was unexpected, given its prominent role in initiating the GzmA cell death pathway.…”
Section: Discussionsupporting
confidence: 93%
“…5,25 Given the lack of ROS generation as a trigger, it is unclear whether mGzmA would induce SET cleavage in vivo; however, we found that target cell treatment with recombinant mGzmA or GzmB with Pfp did induce cleavage of the SET complex component Ape-1 in vitro (data not shown). This correlates with reports that WT, GzmA À / À , GzmB À / À and GzmA À / À B À / À CTL were equally able to induce Ape-1 cleavage in target cells, 12 suggesting that SET complex cleavage may not always be a GzmA-specific event.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations